Implementation of Health Information Systems in Romania - Mihalas, G. I.; Bazavan, M.; Farcas, D. D. (Methods of Information in Medicine, 2006)
Objectives: The paper aimed to present and analyze the development of Healthcare Information Systems in Romania during the last decade. The first part was dedicated to the analysis of a large national project, HMIS – Healthcare Management Information System, and the second to the current state of the hospital information systems and primary care systems.Methods: The approach of a “case study” was used. The description of the HMIS project comprised the objectives and its structure, implementation, results and lessons learned. This is followed by a classical short presentation of the current state at the hospital and primary care levels.Results: The very modest results of the HMIS project were critically analyzed, listing the ‘failure factors’ at various moments, both weak points of the project as well as the consequences of the structural-organizational changes within the Romanian healthcare system during the implementation. However, mainly positive results were registered in the last years at lower levels, hospitals and primary care, which can also partially be interpreted as ‘lesson learned’.Conclusions: There are several things to be learned from the Romanian experience. Healthcare information system analysis is quite complex. Obtaining better results requires several additional measures including better education and training, adopting standards and appropriate quality assessment tools.
Keywords: Healthcare information systems; system analysis; hospital information system; primary care systems